Multiple Intelligence of Early Children in Creative Dance - Wulandari, Hayani; Muqodas, Idat; Nikawanti, Gia; Ardiyanti, Dhea (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
Early Childhood Education (PAUD) activities are designed to optimize all aspects of child development including multiple intelligence. Some of them are kinesthetic intelligence, musical intelligence, interpersonal intelligence, and intrapersonal intelligence. This aspect of multiple intelligences can be developed through creative dance. The purpose of learning creative dance in this study is not to make children professional dancers, but to use it as a learning method. This study aims to describe the dual intelligence of early childhood in the process of implementing creative dance learning. Through a qualitative descriptive research method, the researcher revealed the multiple intelligences of children in the implementation of creative dance learning by a Kindergarten teacher in Purwakarta. The subjects in this study were teachers and early childhood with an age range of 5-6 years, totaling 20 children. Data collection was carried out through observation, interviews, documentation and strengthened by literature study. The data obtained were then analyzed descriptively with the stages of data reduction, data presentation, and verification. The results showed that learning creative dance can develop multiple intelligence in children.